Arginine and Glutamate-rich 1 (ARGLU1) Interacts with Mediator Subunit 1 (MED1) and Is Required for Estrogen Receptor-mediated Gene Transcription and Breast Cancer Cell Growth - Dingxiao Zhang; Pingping Jiang; Qin‐Qin Xu; Xiaoting Zhang (2011)
Estrogen receptor is a nuclear receptor superfamily member of transcriptional activators that regulate gene expression by recruiting diverese transcriptional coregulators. The Mediator complex is a central transcriptional coactivator complex that acts as a bridge between transcriptional activators and RNA polymerase II. MED1 (Mediator subunit 1) is the key Mediator subunit that directly interacts with estrogen receptor to mediate its functions both in vitro and in vivo. Interestingly, our previous biochemical analyses indicated that MED1 exists only in a subpopulation of the Mediator complex that is enriched with a number of distinct Mediator subunits and RNA polymerase II. Here, we report ARGLU1 as a MED1/Mediator-associated protein. We found that ARGLU1 (arginine and glutamate rich 1) not only colocalizes with MED1 in the nucleus, but also directly interacts with a far C-terminal region of MED1. Reporter assays indicate that ARGLU1 is able to cooperate with MED1 to regulate estrogen receptor-mediated gene transcription. Importantly, ARGLU1 is recruited, in a ligand-dependent manner, to endogenous estrogen receptor target gene promoters and is required for their expression. Furthermore, by ChIP-reChIP assay, we confirm that ARGLU1 and MED1 colocalize on the same estrogen receptor target gene promoter upon estrogen induction. Moreover, we found that depletion of ARGLU1 significantly impairs the growth, as well as anchorage-dependent and -independent colony formation of breast cancer cells. Taken together, these results establish ARGLU1 as a new MED1-interacting protein required for estrogen-dependent gene transcription and breast cancer cell growth.